2006
DOI: 10.1037/0893-164x.20.2.117
|View full text |Cite
|
Sign up to set email alerts
|

College drinking behaviors: Mediational links between parenting styles, impulse control, and alcohol-related outcomes.

Abstract: Mediational links between parenting styles (authoritative, authoritarian, permissive), impulsiveness (general control), drinking control (specific control), and alcohol use and abuse were tested. A pattern-mixture approach (for modeling non-ignorable missing data) with multiple-group structural equation models with 421 (206 female, 215 male) college students was used. Gender was examined as a potential moderator of parenting styles on control processes related to drinking. Specifically, the parent-child gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
157
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(180 citation statements)
references
References 59 publications
21
157
0
2
Order By: Relevance
“…Findings were consistent with those reported by Patock-Peckham and colleagues (Patock-Peckham et al, 2011;Patock-Peckham & Morgan-Lopez, 2006), and Kabbani and Kambouropoulos (2013) in non-dependent, college drinkers. The magnitude of the mediation effect was smaller in this sample of treatment-seeking inpatients, compared to college students (Kabbani & Kambouropoulos, 2013) and is consistent with Gullo et al (2010), where drinking refusal self-efficacy was compared between college drinkers and dependent drinkers.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Findings were consistent with those reported by Patock-Peckham and colleagues (Patock-Peckham et al, 2011;Patock-Peckham & Morgan-Lopez, 2006), and Kabbani and Kambouropoulos (2013) in non-dependent, college drinkers. The magnitude of the mediation effect was smaller in this sample of treatment-seeking inpatients, compared to college students (Kabbani & Kambouropoulos, 2013) and is consistent with Gullo et al (2010), where drinking refusal self-efficacy was compared between college drinkers and dependent drinkers.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported that perceived impaired control mediates the association between rash impulsiveness and problem drinking (Kabbani & Kambouropoulos, 2013;Patock-Peckham, King, Morgan-Lopez, Ulloa, & Filson Moses, 2011;Patock-Peckham & Morgan-Lopez, 2006). The magnitude of the mediation effect ranges from β = .09 (Kabbani & Kambouropoulos, 2013) Past studies investigating mediation have sampled non-dependent, college drinkers.…”
Section: Introductionmentioning
confidence: 99%
“…Nagoshi showed that after controlling for gender, age, impulsivity, venturesomeness, depression, irrational beliefs, alcohol norms and expectancies and reasons for drinking, Part 3 scores significantly predicted alcohol-related problems but not alcohol consumption. PatockPeckham and colleagues found that Part 3 score was significantly associated with both alcohol use and related problems in a model above and beyond parental rearing style and self-regulation (2001) and in a separate report, above and beyond parental rearing style and impulsiveness (Patock-Peckham and Morgan-Lopez, 2006). Part 2 of the ICS was used instead of Part 3 in the present study.…”
Section: Introductionmentioning
confidence: 76%
“…Nagoshi has found Part 3 of the ICS to be reliable for use with undergraduates (Nagoshi, 1999). With respect to validity in this population, Nagoshi, Patock-Peckham and colleagues have consistently found Part 3 scores to be significantly correlated with both alcohol use and alcohol-related problems (PatockPeckham et al, 1998;Nagoshi, 1999;Patock-Peckham et al, 2001;Patock-Peckham and Morgan-Lopez, 2006). In these studies, Part 3 scores were found to be predictive of problem drinking in cross-sectional models while controlling for a number of different variables.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation